Experimental study on Cervi Cornu on Adjuvant Arthritis in rats - Ji-Won, Shin; Jai-Young, Park; Hee-Soo, Park (Korean Pharmacopuncture Institute, 2002)
Objective: To investigate effects of Cervi Cornu on Adjuvant Athritis in rats, the edema inhibit rate, the anaJgesic effects, the number of WBC, RA facter, Platelet, the quantity of CRP, total protein, albumin and globuline in the blood serum were measured in the arthritis part. Results: The results obtained as fonows ; 1. After arthritis of Sprague dawley(SD) rats was induced by injecting Freund's complete adjuvant for 2 weeks, any treatment was not for Control group, acupunctured for Treat Ⅰ group. normal saJine was ora] administrated for the Treat Ⅱ group, Cervi Cornu Ex. was oral administrated for Treat Ⅲ, and Cervi Cornu Herbal-acupullcture was injected for Trea Ⅳ group during 2 weeks every other day. Selected point was on pressure pain point in both groups. And then the edema inhibit rate were checked. The edema inhibit rate was in Treat I group, Treat IV group, in Treat III. there was significance in the edema inhibit rate between Control group and Treat group, in order of Treat Ⅰ, Ⅳ, Ⅲ.(p<0.05) 2. The analgesic effects was (gm) in Control group. (gm) in Treat Ⅰ group. (gm) in Treat Ⅲ group and (gm) in Treat Ⅳ group. There was significance in the analgesic effects between Control group and Treat group(p<0.05) 3. The number of WBC was (㎕) in control Group, (㎕) in Treat Ⅰ group, (㎕) in Treat Ⅱ Group and (㎕) in Treat Ⅳ group. There was significance in the number of WBC between Control group and Treat group(p<0.05) 4. The content of total protein in the blood serum were g/dl in control group, g/dl in Treat I group, g/dl in Treat Ⅲ group and g/dl in Treat IV group. There was significance in The content of total protein in the blood serum between Control group and Treat group(p<0.05) 5. The contests of albumin in the blood serum were g/dl in the Control group, g/dl in Treat Ⅰ group, g/dl in Treat Ⅱ group, g/dl in Treat Ⅲ group, g/dl in Treat IV group. There was no significance in The content of albumin in the blood serum between Control group and Treat group(p<0.05) 6. The contests of globulin in the blood semm were g/dl in the Control group, g/dl in Treat Ⅰ group, g/dl in Treat IV group. There was significance in The content of globulin in the blood serum between Control group and Treat group(p<0.05) 7. The numbers of RA factor were IU/ml in Control group and IU/ml in Treat Ⅱ group. There was significance inThe numbers of RA factor between Control group and Treat group(p<0.05) 8. The numbers of platelet were /㎕ in Control group, /㎕ in Treat Ⅰ group, /㎕ in Treat Ⅱ group, /㎕l in Treat Ⅲ group, /㎕ in Treat Ⅳ group. There was no significance in The numbers of platelet between Control group and Treat group(p<0.05) 9. The quantity of CRP were mg/ml in Control group, mg/ml in Treat Ⅰ group, mg/ml in Treat Ⅱ group, mg/ml in Treat.....